2018
DOI: 10.1136/bmj.k4306
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient temperature and mortality risk and burden: time series study in 272 main Chinese cities

Abstract: ObjectivesTo examine the association between temperature and cause specific mortality, and to quantify the corresponding disease burden attributable to non-optimum ambient temperatures.DesignTime series analysis.Setting272 main cities in China.PopulationNon-accidental deaths in 272 cities covered by the Disease Surveillance Point System of China, from January 2013 to December 2015.Main outcomes and measuresDaily numbers of deaths from all non-accidental causes and main cardiorespiratory diseases. Potential eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
239
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 280 publications
(304 citation statements)
references
References 37 publications
(63 reference statements)
29
239
2
1
Order By: Relevance
“…Some studies have shown that the risk of extreme cold temperature was consistently higher than the risk of heat temperature on human health. Chen et al [9] reported that 1.14% and 0.63% of non-accidental total mortality was attributable to extreme cold and extreme heat temperatures, respectively. In UK regions, cold-related mortality accounts for more than one order of magnitude than heat-related mortality.…”
Section: Of 12mentioning
confidence: 99%
“…Some studies have shown that the risk of extreme cold temperature was consistently higher than the risk of heat temperature on human health. Chen et al [9] reported that 1.14% and 0.63% of non-accidental total mortality was attributable to extreme cold and extreme heat temperatures, respectively. In UK regions, cold-related mortality accounts for more than one order of magnitude than heat-related mortality.…”
Section: Of 12mentioning
confidence: 99%
“…The results indicated that changes in PM 2.5 concentration due to the implementation of the Action Plan may not have been the main reason for the increase in RD death rates at low PM 2.5 concentrations. Besides PM 2.5 , abnormal ambient temperature was also a critical risk factor for adverse health outcomes [41,42]. Thus, we examined the associations between ambient temperature and respiratory mortality at low PM 2.5 concentrations (see S1 in the online supplementary information).…”
Section: Pre-emission Reduction Periodmentioning
confidence: 99%
“…In this study death has been used as a retrospective measure of the nearness to death effect and its consequent effect on hospital admissions and bed occupancy. Death and cause of death is sensitive to a variety of environmental parameters, hence, the observation that deaths are both seasonal, and highly volatile and that this volatility is location specific . In this study, Figures and demonstrated this in an Australian context.…”
Section: Discussionmentioning
confidence: 99%